2021
DOI: 10.24057/2071-9388-2021-054
|View full text |Cite
|
Sign up to set email alerts
|

Gis And Remote Sensing: A Review Of Applications To The Study Of The Covid-19 Pandemic

Abstract: The spread of the 2019 novel coronavirus disease (COVID-19) has engulfed the world with a rapid, unexpected, and far-reaching global crisis. In the study of COVID-19, Geographic Information Systems (GIS) and Remote Sensing (RS) have played an important role in many aspects, especially in the fight against COVID-19. This review summarises 102 scientific papers on applications of GIS and RS on studies of the COVID-19 pandemic. In this study, two themes of GIS and RS-related applications are grouped into the six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…It was concluded that the population that emigrated from Wuhan was the main infection source in other cities and provinces (24). After the COVID-19 pandemic rapidly spread across over the world, attempts have been put on the use of geographical analysis to detect the spatio-temporal changes in many countries, especially in the worst-affected countries (25). Using spatial and space-time scan statistics and the Joinpoint analysis, a study in the United States has indicated that higher risks of clustering and incidence of COVID-19 were consistently observed in metropolitan versus rural counties, counties closest to core airports, the most populous counties, and counties with the highest proportion of racial/ethnic minorities (26).…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the population that emigrated from Wuhan was the main infection source in other cities and provinces (24). After the COVID-19 pandemic rapidly spread across over the world, attempts have been put on the use of geographical analysis to detect the spatio-temporal changes in many countries, especially in the worst-affected countries (25). Using spatial and space-time scan statistics and the Joinpoint analysis, a study in the United States has indicated that higher risks of clustering and incidence of COVID-19 were consistently observed in metropolitan versus rural counties, counties closest to core airports, the most populous counties, and counties with the highest proportion of racial/ethnic minorities (26).…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, an advanced technique as remote sensing in the study of COVID-19 pandemic plays an important role in the fight against the COVID-19 pandemic.Remote sensing is the process of detecting and monitoring the physical characteristics of an area by measuring its reflected and emitted radiation at a distance (typically from satellite or aircraft). Remote sensing allows acquiring information about the Earth's surface without actually being in contact with it (5). Satellite remote sensing data was used widely by government, humanitarian, and private bodies during the pandemic (6).…”
Section: Introductionmentioning
confidence: 99%
“…A crucial tool for analysing the spatial pattern of spatial objects is a spatial statistic. (5). In accordance with Tobler's First Law of Geography, epidemiological research have effectively used commonly used statistics for spatial autocorrelation analysis, such as global spatial statistics (Moran's I, Getis-Ord G* and Geary's C) and local indicators of spatial association (LISA) (6)(7)(8)(9) in general, and in the investigation of COVID-19's transmission (10)(11)(12) and hand-foot-andmouth disease (13,14) in particular.…”
Section: Introductionmentioning
confidence: 99%